Some Non-Traditional Steps in Laboratory Classes for Engineering Curriculum - Chattopadhyay, A. B.; Ghosh, A. K. (Journal of Engineering Education Transformations, 1994)
It has been learnt that the traditional steps for conducting laboratory classes in engineering curriculum, e.g. supplying instruction sheets for each experiment to the students, checking the working procedures followed by the students etc.